The press: engine of a mini-renaissance in Zanzibar (1860-1920) - Sadgrove, Philip C. (History of printing and publishing in the languages and countries of the Middle East, 2004)
Keywords: Imprimerie – Zanzibar

The Sultan and the palace in the cultural transformation of Zanzibar, 1840-1920 - Sadgrove, Philip C. (al-Mu’tamar al-Duwalī : al-Dawr al-ʿUmānī fī ‘l-Sharq al-Ifrīqī, 11-13 Dec. 2012. Buḥūth al-Mu’tamar, 2014)

CUSTERS, M. H.- Al-Ibadiyya. A bibliography. Volume 1: Ibadis of the Mashriq; Volume 2: Ibadïs of the Maghrib (incl. Egypt); Volume 3: Secondary literature - Sadgrove, Philip C. (Bibliotheca Orientalis, 2009)
Keywords: Recension

CUSTERS, M. H.- Ibadi publishing activities in the East and in the West c. 1880-1960s. An attempt to an inventory, with references to related recent publications - Sadgrove, Philip C. (Bibliotheca Orientalis, 2009)
Keywords: Recension

From Wādī Mīzāb to Unguja, Zanzibar’s scholarly links - Sadgrove, Philip C. (2001)
This paper discusses the links, through correspondence found in the Zanzibar archives, in the late 19th and early 20th century maintained between the remote community of Wādī Mīzāb, in the person of the great Algerian Ibāḍī scholar, Muḥ. b. Yūsuf Iṭfayyish (1820/1-1914) and the Sultans of Zanzibar. The letters, in an obscure classical format, inter alia raise questions of patronage, the precarious impecunious position of scholars and problems of publishing. The paper was kindly made available to me before its publication. Sadgrove also treats al-Maṭb. al-Bārūniyya in Cairo and al-Maṭb. al-Sulṭāniyya at Zanzibar. See Custers 2006a.
FMC Institute for the Study of Islamic Thought in Africa
Keywords: Zanzibar

From Wadi Mizab to Unguja: Zanzibar’s Scholarly Links - Sadgrove, Philip C. (The transmission of learning in Islamic Africa, 2004)
Keywords: Zanzibar

A survey of Arabic-character publications printed in Egypt during the period 1238-1267 (1822-1851) - Hsu, Cheng-Hsiang (History of printing and publishing in the languages and countries of the Middle East, 2004)
Keywords: Bibliographie